GenoType®® MTBDRplus compared with conventional drug-susceptibility testing of Mycobacterium tuberculosis in a low-resistance locale. (March 2011) - Gitti, Zoe; Mantadakis, Elpis; Maraki, Sofia; Samonis, George
Aim: To determine the diagnostic accuracy of Geno Type ®® MTBDRplus compared with conventional proportional method (PM) drug susceptibility testing (DST) for detecting drug resistance of Mycobacterium tuberculosis (MTB) clinical isolates derived from the University Hospital of Heraklion, Crete, Greece.Methods: All MTB clinical isolates obtained between January 2000 and May 2009 were tested prospectively using the PM DST. All isolates were also tested either prospectively (strains isolated after January 2006; n = 140) or retrospectively (January 2000––December 2005; n = 81) using MTBDRplus.Results: Among the 221 MTB isolates tested, 19 were resistant to isoniazid based on PM DST. The MTBDRplus assay identified 18 INH-resistant strains. Of these, 12 strains gave positive hybridization results with the mutation-specific probe katG Ser315Thr. The other six INH-resistant strains carried the mutation 15C→→T in the inhA promoter region. One INH-sensitive strain, as determined by PM DST, had a katG gene mutation. The sensitivity, specificity, and positive and negative predictive values of MTBDRplus for INH were 89.5, 99.5, 94.7 and 99%, respectively. The single rifampicin-resistant strain that was also the only multidrug resistance isolate gave a positive hybridization result with the mutation-specific probe MUT1: D516V, which confers resistance to rifampicin.Conclusion: Despite the advantages of MTBDRplus (turn-around time of only 1 working day) compared with PM DST, the latter is still required in every case of a MTB clinical isolate, as the molecular assay does not detect 100% of drug resistance, especially INH resistance.